Kollektiv für sozialistisches Bauen. Proletarische Bauausstellung. Collective for socialist architecture. Proletarian building Exhibition. - (:unkn) unknown (Spector Books, 2015)
Im Jahr 1931 fand in Berlin die Proletarische Bauausstellung statt. Das Kollektiv für sozialistisches Bauen entwickelte sie als Gegenposition zur Deutschen Bauausstellung. Wohnungsfrage hat historische Originaldokumente neu erschlossen und in einer Tagung in Zusammenarbeit mit dem projekt bauhaus zur Diskussion gestellt. Forschungszugänge über einzelne Personen wie Arthur Korn, Alexander Altberg und Hermann Duncker sowie die Verbindungen zu Projekten wie CIAM, Marxistische Arbeiterschule und Bauhaus, aber auch die Beziehungen in die UdSSR lassen die Netzwerke und politischen Haltungen der Architekturmoderne sichtbar werden.

The housing question is an universal question. Everywhere, it speaks differently but directly to the challenges that define our times: social inequality, ecological crisis, displacement, asylum, migration, and privatization. This volume interprets the neoliberal context as a defining condition for contemporary housing. The book consists of two parts: a series of essays by authors from the fields of architecture, anthropology, economy, and literature depicting various, often-contradicting contexts, and, part two, an Atlas of global housing that takes the neoliberal turn as its starting point. The essays shed light on the challenges and conflicts of contemporary housing production and the "Atlas" serves as a starting point to discuss and think about housing produced and consumed under a neoliberal doctrine.
Keywords: Wohnungswesen; Stadtsoziologie; Wohnungsbau; Wohnraum; Ausstellung; Sozialismus